Effect of moisture absorption on the mechanical properties of soil buried kenaf fibre reinforced unsaturated polyester composites - Rashdi, Abdalla A. Ab.; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Abdan, Khalina (2009)
Over the last decade, composites of Unsaturated polyester reinforced with natural fibres have received ever increasing attention, both from the academic world and from various industries owing to various desirable properties including high specific strength, high specific stiffness. But unfortunately, natural composites absorb moisture in humid environments which affects their mechanical properties. Since moisture absorption is a matter of concern moisture absorption of soil buried kenaf fibre reinforced unsaturated polyester composites studied. Kenaf fibres/ unsaturated polyester reinforced composites containing (10%, 20% and 30%) weight percentage of fibre made and the moisture absorption in them studied by soil burial for 4 months. It found that percentage of moisture uptake increased as the weight percentage of fibre content increased due to the high cellulose content. The properties of interest were the tensile strength. The tensile properties found to decrease with increase in percentage moisture uptake. The water absorption found to follow the kinetics and mechanisms described by Fick’s theory.